Error Elimination Algorithm in 3D Image Reconstruction - Jin Xian-Hua; Zhao Yuan-Qing (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In process of three-dimensional (3D) reconstruction, effective matching of feature is the key point of accurate reconstruction in later stage. In order to eliminate the error of modeling distortion caused by inaccurate feature matching in the process of 3D image reconstruction, a feature matching error elimination method based on collision detection is presented. A 3D image reconstruction mathematical model is established to operate the solution of image 3D reconstruction and camera space matrix elements of exterior orientation. The error of the feature matching in 3D dynamic modeling is eliminated according to the result of the collision two gray digital images are used to carry out simulation experiment. Experimental results show that the proposed algorithm can effectively eliminate the error of feature matching and improve the accuracy of the modeling. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4250